TERAPI BURNOUT AKADEMIK: REFRAMING MOTIVASI BERSABAR DAN MENCARI RIDHA ALLAH SWT. DALAM MASA STUDI: Kajian Epistemologi Hadits Tarbawi - Izuddin, Azmi; Thobroni , Ahmad Yusam (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2025)
The acquisition of knowledge is a religious commandment incumbent upon Muslims for their own benefit. Yet, student academic burnout arises not only from study load but also from a crisis of meaning within modern educational epistemology, which perpetuates a dichotomy between revealed (naqli) and rational (aqli) knowledge. This bifurcation commodifies knowledge, divorcing it from its spiritual essence and triggering a sense of emptiness that culminates in burnout. This study seeks to deconstruct academic burnout by offering an epistemological therapy derived from the tarbawi (educational) hadiths of the Prophet, focusing on the motivational reframing of patience and the pursuit of God's pleasure in seeking knowledge. Employing a qualitative method with a literature review approach, the research conducts a thematic analysis of hadiths related to the virtues of knowledge, patience, and seeking divine approval. The results demonstrate that these hadiths provide a fundamental epistemological solution to academic burnout by challenging the knowledge dichotomy. They establish two core principles: firstly, patience functions as a cognitive-spiritual framework that enables a transformative reframing of academic pressures. Secondly, seeking God's pleasure forms the foundational epistemology for a serene and meaningful educational system.